G351 Outcome of non-cardiac surgery in children with congenital heart disease performed outside a cardiac centre. (7th April 2014) - Ng, SM; Yates, R; Kelsall, AWR
Abstract : Background: Approximately 30% of children with congenital heart disease (CHD) require surgery within the first year of life for extracardiac anomalies. CHD increases short- and long-term mortality risks for non-cardiovascular procedures 1 . Whether surgery is conducted in a local hospital or a specialist cardiac centre remains a matter of debate. This study reviews the outcome of children with CHD undergoing non-cardiac surgery in a single institution conducted by experienced paediatric surgeons, anaesthetists and intensivists working alongside paediatricians with expertise in cardiology. Methods: A retrospective case note review of children under 16 years of age, with confirmed CHD, undergoing a surgical/investigative procedure requiring general anaesthesia (GA) between 2010 and 2012. Patients were identified from outpatient and surgical databases. Results: Over 3 years, 117 patients with CHD underwent 240 procedures requiring GA. 36 procedures were performed in the high-risk (HR) group, 135 in intermediate-risk (IR) and 69 in low-risk (LR) groups. The cumulative mortality rates at 7- and 30-days were 0% and 0.4%, respectively. The post-operative complication rate was 16.6% (40/240 procedures) – 19.4%, 20.7% and 7.2% in the HR, IR and LR groups respectively. There were planned admissions to the paediatric intensive care unit (PICU) after 41 procedures (17.1%). The mean duration of PICU stay was 9.8 days, 1.5 days and 1 day in the HR, IR and LR groups, respectively. The duration of hospital stay across all risk groups ranged between 0–71 days. The mean duration of hospital stay for the HR, IR and LR groups was 5.8, 6.4 and 2.2 days, respectively. There was one death, in a child whose resuscitation status changed with the results of investigations to a palliative care approach. Conclusion: This study demonstrates that procedures requiring GA on patients with CHD can be safely conducted in a non-cardiac centre. This requires close liaison and careful planning between all specialist clinicians involved in the child's care especially the paediatric cardiologist and paediatrician with expertise in cardiology. This study confirms it is safe with appropriate communication to provide treatment, including non-cardiac surgery, close to the child's home in line with the Safe and Sustainable standards 2 . References: White MC, Peyton JM. Anaesthetic management of children with congenital heart disease for non-cardiac surgery. Cont Ed in Anaesthesia, Critical Care & Pain 2012. 12:17–22 Safe and Sustainable Review of Children's Congenital Heart Services in England: Report of the public consultation (24 August 2011)